In the Shadow of Gillian Rose: Truth as Education in the Hegelian Philosophy of Rowan Williams - Howes, Rebekah (Political theology, 2018)
Rowan Williams, ex-Archbishop of Canterbury (2002-2012), is a polymath of remarkable breadth and depth. But there remains at least one area in which his philosophical work has gone relatively unacknowledged and that is his view of education. My aim here is to explore a philosophically nuanced notion of truth as education in his work by examining its indebtedness to Hegel, and the recent Hegelianism of Gillian Rose. I argue that not only does a radical re-reading of the negative by Williams shape a formidable social and political critique but that therein the question of the Absolute is renewed in and for our time as one of learning.